Numerical simulation of ignition of a typical gel fuel particle, based on organic polymer thickener, in a high-temperature air medium - Glushkov D. O. Dmitry Olegovich; Kosintsev A. G. Andrey Georgievich; Kuznetsov G. V. Geny Vladimirovich; Vysokomorny (Vysokomorniy) V. S. Vladimir Sergeevich (2021, 2021)
Title screen